Swarm Projects: Beyond the Metaphor - Parrend, Pierre; Masai, Pierre; Zanni-Merk, Cecilia; Collet, Pierre (Swarm Intelligence Based Optimization, 2014)
Swarming has become a management tool for letting individuals cooperate in order to generate emergent solutions to difficult issues in organizations. Beyond the buzzword, we claim that swarming actually matches specific project management practices having a great potential for improving project success. Swarming project management is defined, and the way it complements traditional and agile project management schemes is analysed. Metrics for evaluation of management practices are defined: required practices - practices that lead to failure if not implemented - success practices - practices that good teams put in place - and silver bullets - practices having a measurably significant impact on success. The analysis is performed through a controlled experiment involving 52 computer science students at the bachelor level, in the context of a 4 month development project involving 8 parallel teams working on the same software project.